Desempenho de reatores biológico com leito móvel no pós-tratamento de reator anaeróbio - Souza, Flávia Vitoi Rosa de (2019)
This work evaluated the performance of a moving bed biofilm reactor (MBBR) as an anaerobic system post-treatment, characterizing the carrier used and calculating the main parameters used to design sewage treatment plants of type MBBR. The bench system operated for 152 days, and was composed of two MBBR reactors that operated in four different configurations, that is, with 2 and 4 hours of hydraulic retention time (HRT) and with 50 and 70% percent of carrier. The pilots were fed with synthetic effluent with a mean affluent COD concentration of about 200 mg/L and the dissolved oxygen of the MBBR was maintained close to 2.0 mg/L. The characterization of the carrier was carried out, finding average specific surface area of 507 m² / m³. Biomedia was able to retain a high amount of biomass on its surface, reaching values of up to 14.6 gSV/m², for the condition of 50% of filling, showing that it is efficient for this use. The average COD removal efficiency ranged from 66.7% to 75.9%, but according to ANOVA, there was no statistically significant difference between the four phases. The organic loading rate (OLR) ranged from 4.69 to 10.28 gDQOt / m².day, with a linear relationship to treatment efficiency observed. It was also observed the occurrence of partial nitrification of the effluent, reaching up to 45.9% efficiency of ammoniacal nitrogen removal. It was possible to conclude that it is feasible to use an MBBR reactor for post-treatment of anaerobic reactor, obtaining a COD removal efficiency of more than 70%, the optimal working point being 2.0 h HRT and 50% of carrier